Membangun Komunitas Iman Melalui Media Sosial Dengan Menggunakan Platfrom Yang Menarik - Theresiani Bheka; Emmeria Tarihoran (Jurnal Magistra, 2024)
Social media has an important role in building and strengthening religious communities. Social media can be used to build and strengthen believers, in the current digital era social media has become a platform that is widely used by many people to interact and share information as well as a means to develop faith and strengthen brotherhood between religious communities. . In a religious context, social media can be a powerful tool for spreading religious messages and building solid religious communities. In this case the discussion includes community, religion and social media. Through this article, it is hoped that readers can find new inspiration and motivation to build a solid and connected religious community through social media. After all of the things above have been touched on, by using the literature study method, this article offers a solution that building a community of believers is not only through meetings or face-to-face encounters but can be done through social media.